A Pilot Study of the Association of Markers of Cholesterol Synthesis with Disturbed Sleep in Smith-Lemli-Opitz Syndrome. Issue 5 (June 2016) - Freeman, Kurt A.; Olufs, Erin; Tudor, Megan; Roullet, Jean-Baptiste; Steiner, Robert D.
ABSTRACT: Objective: Smith-Lemli-Opitz syndrome (SLOS) is a rare genetic disorder characterized by cholesterol synthesis impairment. A host of physical, developmental, and behavioral presentations are associated with SLOS, many of which have been related with disorder severity. Sleep disturbance is commonly reported in SLOS. This study is the first to examine the association between sleep disturbance and biomarkers of cholesterol synthesis defect. Method: Twenty youth with SLOS participated. Biomarkers of cholesterol synthesis were obtained, including plasma sterols (i.e., 7-dehydrocholesterol, 8-dehydrocholesterol, and cholesterol), mevalonic acid, and 24-S hydroxycholsterol. A ratio of plasma cholesterol precursors to cholesterol levels was used as a measure of biochemical severity. Parents reported their children's sleep problems using the Children's Sleep Habits Questionnaire. Results: Most markers of cholesterol synthesis disruption were associated with overall sleep disturbance. Biochemical severity of SLOS was also associated with specific sleep problems (e.g., decreased sleep duration and increased sleep onset delay) and was identified as a significant predictor of these factors. Conclusion: This study is the first to demonstrate associative relationships between cholesterol levels and sleep disturbance in youth with SLOS. These results add to the current understanding of how cholesterol levels may contribute to the behavioral phenotype of SLOS. These findings may inform future studies related to the role cholesterol synthesis defects play in the behavioral phenotype of SLOS and, subsequently, modalities of intervention for behavioral symptoms.